Cognitive-pragmatic features of translating English-language economic texts. - Frumkina , Aryna (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2026)
The article focuses on the study of cognitive-pragmatic features of translating English-language economic texts into Ukrainian within the framework of contemporary professional discourse. The relevance of the research is determined by the growing role of economic communication in the globalized information space and the need to ensure adequate translation of economic texts belonging to various genres. The aim of the article is to analyze the lexical-stylistic, metaphorical, and grammatical features of English-language economic texts and to substantiate translation strategies aimed at achieving functional equivalence and communicative effectiveness in Ukrainian translation. The theoretical framework of the study is based on the principles of modern translation studies, cognitive linguistics, and discourse studies, in particular the concepts of the functional approach to translation, cognitive-pragmatic analysis, and discourse theory. The article combines theoretical analysis with a practical examination of translation solutions based on authentic English-language economic texts. The practical part of the study involves an analysis of the translation of terminological units, set terminological collocations, idiomatic verb constructions, metaphorical models, and grammatical structures characteristic of English-language economic discourse. Special attention is paid to the problem of polysemy of economic terms, conceptual differences in the representation of economic notions, as well as to the translation of metaphors performing cognitive and pragmatic functions. The results of the study demonstrate that adequate translation of English-language economic texts is possible only through a comprehensive functional approach that integrates contextual interpretation of terms, the application of lexical-semantic and syntactic transformations, and consideration of genre-specific and pragmatic parameters of the text. The practical value of the article lies in the possibility of applying the obtained results in the training of specialists in specialized translation and in further research on economic discourse within the framework of translation studies.